Peritoneal Spread of Ovarian Cancer Harbors Therapeutic Vulnerabilities Regulated by FOXM1 and EGFR/ERBB2 Signaling - Parashar, Deepak; Nair, Bindu; Geethadevi, Anjali; George, Jasmine; Nair, Ajay; Tsaih, Shirng-Wern; Kadamberi, Ishaque P; Gopinadhan Nair, Gopa Kumar; Lu, Yiling; Ramchandran, Ramani; Uyar, Denise S; Rader, Janet S; et al. (Cancer research (Chicago, Ill.), 2020)
Peritoneal spread is the primary mechanism of metastasis of ovarian cancer, and survival of ovarian cancer cells in the peritoneal cavity as nonadherent spheroids and their adherence to the mesothelium of distant organs lead to cancer progression, metastasis, and mortality. However, the mechanisms that govern this metastatic process in ovarian cancer cells remain poorly understood. In this study, we cultured ovarian cancer cell lines in adherent and nonadherent conditions and analyzed changes in mRNA and protein levels to identify mechanisms of tumor cell survival and proliferation in adherent and nonadherent cells. EGFR or ERBB2 upregulated ZEB1 in nonadherent cells, which caused resistance to cell death and increased tumor-initiating capacity. Conversely, Forkhead box M1 (FOXM1) was required for the induction of integrin β1, integrin-α V, and integrin-α 5 for adhesion of cancer cells. FOXM1 also upregulated ZEB1, which could act as a feedback inhibitor of FOXM1, and caused the transition of adherent cells to nonadherent cells. Strikingly, the combinatorial treatment with lapatinib [dual kinase inhibitor of EGFR (ERBB1) and ERBB2] and thiostrepton (FOXM1 inhibitor) reduced growth and peritoneal spread of ovarian cancer cells more effectively than either single-agent treatment . In conclusion, these results demonstrate that FOXM1 and EGFR/ERBB2 pathways are key points of vulnerability for therapy to disrupt peritoneal spread and adhesion of ovarian cancer cells. SIGNIFICANCE: This study describes the mechanism exhibited by ovarian cancer cells required for adherent cell transition to nonadherent form during peritoneal spread and metastasis. GRAPHICAL ABSTRACT: http://cancerres.aacrjournals.org/content/canres/80/24/5554/F1.large.jpg.